Everyday Beliefs About Emotion Perceptually Derived From Neutral Facial Appearance - Albohn, Daniel N.; Adams, Reginald B. (Frontiers in Psychology, 2020)
The evolution of the human brain and visual system is widely believed to have been shaped by the need to process and make sense out of expressive information, particularly via the face. We are so attuned to expressive information in the face that it informs even stable trait inferences (e.g., Knutson, 1996) through a process we refer to here as the face-specific fundamental attribution error (Albohn, Brandenburg, & Adams, 2019). We even derive highly consistent beliefs about the emotional lives of others based on emotion-resembling facial appearance (e.g., low versus high brows, big versus small eyes etc.) in faces we know are completely devoid of overt expression (i.e., emotion overgeneralization effect: see Zebrowitz, Kikuchi, & Fellous, 2010). The present studies extend these insights to better understand lay beliefs about older and younger adults’ emotion dispositions and their impact on behavioral outcomes. In Study 1, we found that older versus younger faces objectively have more negative emotion-resembling cues in the face (using computer vision), and that raters likewise attribute more negative emotional dispositions to older versus younger adults based just on neutral facial appearance (see too Adams, Garrido, Albohn, Hess, & Kleck, 2016). In Study 2, we found that people appear to encode these negative emotional appearance cues in memory more so for older than younger adult faces. Finally, in Study 3 we exam downstream behavioral consequences of these negative attributions, showing that observers’ avoidance of older versus younger faces is mediated by emotion resembling facial appearance.